Effects of music therapy and music–movement interventions on social withdrawal, parent–child relationship and happiness in children with autism spectrum disorder: a protocol for systematic reviews and meta-analysis - Lirou Wen; Feng Wang; Wen Fen Beh (BMJ Open, 2026)
Introduction Children with autism spectrum disorder (ASD) often experience challenges in social interaction, emotional regulation and parent–child bonding, which can negatively impact overall well-being and happiness. Music therapy, particularly when integrated with movement-based interventions, such as piano training, is increasingly recognised as a promising non-pharmacological approach to enhance social engagement and improve psychological outcomes in this population. Although multiple primary studies and pilot trials have been conducted, the evidence remains fragmented and inconsistent. To date, no comprehensive systematic review has synthesised the effects of music-based interventions on (1) social withdrawal, (2) parent–child relationship quality and (3) subjective happiness in children with ASD. Methods and analysis This protocol adheres to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines. A systematic search will be conducted across PubMed, Web of Science, Scopus, China National Knowledge Infrastructure and Wanfang Data from inception to May 2026. Eligible studies will include randomised controlled trials and quasi-experimental studies evaluating music or music–movement interventions for children with ASD. The primary outcome is social withdrawal, whereas the secondary outcomes are the parent–child relationship and overall happiness assessed using validated measures. Data extraction and risk-of-bias assessments will be conducted independently by two reviewers. Where feasible, quantitative synthesis will be performed using random-effects meta-analysis. Subgroup analyses will explore the influence of age, intervention type and intervention duration. The certainty of evidence will be assessed using the Grading of Recommendations Assessment, Development and Evaluation approach. Ethics and dissemination Ethical approval is not required as this review involves published data only. Findings will be disseminated through peer-reviewed publications, conference presentations and community reports targeting clinicians, therapists and parents. PROSPERO registration number CRD420251132116.